Effects of modified sediments on the growth of submerged macrophyte Vallisneria natans under low light conditions - Xiong, Wenhao; Ma, Xiaowen; Xie, Yonghong; Zeng, Wenwen (Frontiers in Plant Science, 2024)
Submerged plants are an important part of aquatic ecosystems, and the restoration of submerged plants is a key step in the reconstruction of aquatic ecosystems. However, little is known about the role of modified sediments in helping submerged plants recover under low light. In this study, we set up four sediment types and two light intensities to explore the effects of modified sediments on the growth of Vallisneria natans under two low light conditions. The results showed that the independent and interactive effects of light intensity and sediment type significantly affected the biomass, morphology, photosynthetic pigment content and antioxidant enzyme activity of V. natans. At 5% and 20% natural light intensity, the sediment modified with 40% peat soil had a larger root biomass and the highest leaf and root C/N ratio, the sediment modified with 40% vermiculite had a longer root length and more ramets. At 5% natural light intensity, the sediments modified with fly ash had shorter root length and smaller leaf biomass. The sediments modified with fly ash had the greatest chlorophyll content at 20% natural light intensity. It can be concluded that the addition of 40% peat soil or 40% vermiculite in 2 sediment is conducive to the growth of V. natans under low light conditions. Our study indicates the positive effects of the modified sediment on the growth of V. natans under low light conditions, and our study will provide a reference for the restoration of submerged plants in aquatic ecosystems.